Recommendations on RBC Transfusion in Critically Ill Children With Nonlife-Threatening Bleeding or Hemorrhagic Shock From the Pediatric Critical Care Transfusion and Anemia Expertise Initiative. (September 2018) - Karam, Oliver; Russell, Robert T.; Stricker, Paul; Vogel, Adam M.; Bateman, Scot T.; Valentine, Stacey L.; Spinella, Philip C.
Abstract : Objectives: To present the recommendations and supporting literature for RBC transfusions in critically ill children with bleeding developed by the Pediatric Critical Care Transfusion and Anemia Expertise Initiative. Design: Consensus conference series of international, multidisciplinary experts in RBC transfusion management of critically ill children. Methods: The panel of 38 experts developed evidence-based and, when evidence was lacking, expert-based clinical recommendations as well as research priorities for RBC transfusions in critically ill children. The bleeding subgroup included five experts. Electronic searches were conducted using PubMed, EMBASE, and Cochrane Library databases from 1980 to May 2017. Agreement was obtained using the Research and Development/UCLA Appropriateness Method. Results were summarized using the Grading of Recommendations Assessment, Development, and Evaluation method. Results: Transfusion and Anemia Expertise Initiative Consensus Conference experts developed a total of six recommendations focused on transfusion in the critically ill child with acute bleeding. In critically ill children with nonlife-threatening bleeding, we recommend giving a RBC transfusion for a hemoglobin concentration less than 5 g/dL, and be considered for a hemoglobin concentration between 5 and 7 g/dL. In critically ill children with hemorrhagic shock, we suggest that RBCs, plasma and platelets transfusion ratio between 2:1:1 to 1:1:1 until the bleeding is no longer life-threatening. We recommend future studies to develop physiologic and laboratory measures to indicate the need for RBC transfusions, and to determine if goal directed hemostatic resuscitation improves survival. Finally, we recommend future studies to determine if low titer group O whole blood is more efficacious and safe compared with reconstituted whole blood in children with hemorrhagic shock. Conclusions: The Transfusion and Anemia Expertise Initiative Consensus Conference developed pediatric specific recommendations regarding RBC transfusion management in the critically ill child with acute bleeding, as well as recommendations to help guide future research priorities. Abstract : Supplemental Digital Content is available in the text.